Measuring media and information literacy skills: construction of a test - Lopes, P. (2018)
Research on media and information literacy has been growing exponentially over the past years, but it has focused more on the examination of media practices than on the assessment of media and information literacy skills. In this paper we describe the process of designing and implementing a Media and Information Literacy Test comprising 20 items. We present the results of the analysis carried out to validate the items and to construct a scale of media and information literacy skills using Item Response Theory (IRT). Findings indicate that the conceptual framework adopted is adequate to measure media and information literacy and that the test has good discrimination and difficulty parameters. The test is based on a more comprehensive framework used to assess media and information literacy skills than those used in previous studies and can be used on an item-by-item basis. In this sense, it is a novel contribution to current efforts to measure media and information literacy skills.